2018
DOI: 10.1016/j.ebiom.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Circulating Tumor DNA Mutation Profiles in Metastatic Breast Cancer Patients with Multiline Resistance

Abstract: PurposeIn cancer patients, tumor gene mutations contribute to drug resistance and treatment failure. In patients with metastatic breast cancer (MBC), these mutations increase after multiline treatment, thereby decreasing treatment efficiency. The aim of this study was to evaluate gene mutation patterns in MBC patients to predict drug resistance and disease progression.MethodA total of 68 MBC patients who had received multiline treatment were recruited. Circulating tumor DNA (ctDNA) mutations were evaluated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 38 publications
4
91
0
2
Order By: Relevance
“…This mutation, was not detected in the PT and appears to be a sub-clonal mutation that resolved whilst the patient was on Pertuzumab, trastuzumab and docetaxel at time point B3. PIK3CA and FAT1 mutations are frequent in hormone receptor positive patients 28 , as in this case, where the PT was reported as ER+ (5+2). We also observed a mutation in TSC2 at B3 only, just prior to disease progression to her lung.…”
Section: Discussionsupporting
confidence: 58%
“…This mutation, was not detected in the PT and appears to be a sub-clonal mutation that resolved whilst the patient was on Pertuzumab, trastuzumab and docetaxel at time point B3. PIK3CA and FAT1 mutations are frequent in hormone receptor positive patients 28 , as in this case, where the PT was reported as ER+ (5+2). We also observed a mutation in TSC2 at B3 only, just prior to disease progression to her lung.…”
Section: Discussionsupporting
confidence: 58%
“…[ 41 ] BRCA1/2 mutation is related to both breast cancer and ovary cancer. [ 42 ] Breast cancer patients with a family history of breast or ovarian cancer also had an increased risk of subsequent leukemia. [ 43 ] BC survivors with ER-negative/HER2-positive and triple-negative BC (TNBC) had a significantly increased risk of developing a second primary asynchronous CBC.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that PIK3CA mutations were frequently seen in tumors with normally expressed PTEN, ER, PR, and ERBB2 genes, as well as in tumors with nodal involvement. Studies demonstrated that mutations in PIK3CA were more common in hormone receptor-positive and HER2-positive breast cancers [25]. In a recent study by Wu et al, it was shown that PIK3CA mutations were positively associated with ER-positive, PR-positive, and low Ki67 labeling index, and negatively correlated with the triple-negative breast cancer subtype [26].…”
Section: Cancer Type Reference Clinicopathological and Prognostic Parmentioning
confidence: 99%
“…Colon Cancer [15] Nodal metastases, high pathological TNM stage, and lymphatic invasion [16] Decreased risk of peritoneal metastases [17,18] Diffuse-type and poorly differentiated gastric cancers and peritoneal recurrence Not associated with patient outcomes such as survival [19,20] Not associated with the overall survival [21] Increased five-year relapse-free interval [22,23] Against anti-EGFR antibodies [24] Poor prognosis Breast Cancer [14] Nodal involvement [25] Hormone receptor positive and HER2-positive status [26,27] ER-positive, PR-positive, low Ki67 labeling index and negatively correlated with triple-negative breast cancer subtype [28,29] Poor survival rates [30] Mutations in exon 9 are associated with poor prognosis but mutations in exon 20 are associated with better prognosis [31] Reduced disease-free survival [32] Risk factors for progression-free survival [33] Poor survival [34][35][36][37] Better survival [30] Exon 9 mutations are independently associated with early recurrence and death, whereas exon 20 PIK3CA mutations are associated with optimal prognosis [38][39][40][41] Resistant to antibody-based therapeutic therapy and chemotherapy Saal et al were the first to report a definite clinicopathological correlate of PIK3CA mutations in breast cancer [14]. They reported that PIK3CA mutations were frequently seen in tumors with normally expressed PTEN, ER, PR, and ERBB2 genes, as well as in tumors with nodal involvement.…”
Section: Cancer Type Reference Clinicopathological and Prognostic Parmentioning
confidence: 99%